Clinical grade lentiviral vector purification and quality control requirements. Issue 12 (15th March 2022) - Shi, Ruina; Jia, Shenghua; Liu, Huwei; Nie, Honggang
Abstract : Lentiviral vectors have been proven to be a powerful tool in gene therapies that includes the ability to perform long‐term gene editing in both dividing and non‐dividing cells. In order to meet the rising demand for clinical‐grade lentiviral vectors for future clinical trials and requirements by regulatory agencies, new methods and technologies were developed, including the rapid optimization of production and purification processes. However, gaps still exist in achieving ideal yields and recovery rates in large‐scale manufacturing process steps. The downstream purification process is a critical step required to obtain a sufficient quantity and high‐quality lentiviral vectors products, which is challenged by the low stability of the lentiviral vector particles and large production volumes associated with the manufacturing process. This review summarizes the most recent and promising technologies and enhancements used in the large‐scale purification process step of lentiviral vector manufacturing and aims to provide a significant contribution towards the achievement of providing sufficient quantity and quality of lentiviral vectors in scalable processes.